Changes of soil and vegetation characteristics caused by landscape rehabilitation earthworks on alkaline grasslands - Novák, Tibor József; Csontos, Bianka (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
More than 500 km earth constructed channels and dikes – former irrigation and rice plantation systems – were rebuilt as part of a landscape rehabilitation project in the Hortobágy National Park (Hungary) between 2003 and 2007. Moving of material and disturbance of soil horizons caused considerable changes in soil and vegetation characteristics as well. Basic soil properties (pH, organic content, CaCO3 content and grain size distribution) were determined in five locations from 3 different surface types such as control, filled ditch and planed dike. At one location also vegetation characteristics were surveyed in totally 36 0,4x0,4 m plots. 18 were situated on disturbed surface, while 18 were located on undisturbed, as control. For statistical evaluation of differences paired samples t-test as parametric (for soil properties) and Man-Whitney U test as nonparametric (for vegetation relative indicator values) was used. By pH (in average by 1,6 higher), grain size distribution (5,5% more clay, 0,9% more silt, and 6,4% less fine sand) and organic content (2,7% less) disturbed sampling sites differed significantly from control. In vegetation of disturbed sampling sites higher species diversity, but lower average naturalness values, and lower salt tolerance values were detected, while other ecological indicator values showed no significant difference. Proportion of therophytes almost doubled on disturbed sampling sites.